UK biobank: Enhanced assessment of the epidemiology and long-term impact of coronavirus disease-2019 - Qi Feng; Ben Lacey; Jelena Bešević; Wemimo Omiyale; Megan Conroy; Fenella Starkey; Catherine Calvin; Howard Callen; Laura Bramley; Samantha Welsh; Allen Young; Mark Effingham; et al. (Cambridge University Press, 2023)
UK Biobank is an intensively characterised prospective cohort of 500,000 adults aged 40-69 years when recruited between 2006 and 2010. The study was established to enable researchers worldwide to undertake health-related research in the public interest. The existence of such a large, detailed prospective cohort with a high degree of participant engagement enabled its rapid repurposing for coronavirus disease-2019 (COVID-19) research. In response to the pandemic, the frequency of updates on hospitalisations and deaths among participants was immediately increased, and new data linkages were established to national severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing and primary care health records to facilitate research into the determinants of severe COVID-19. UK Biobank also instigated several sub-studies on COVID-19. In 2020, monthly blood samples were collected from approximately 20,000 individuals to investigate the distribution and determinants of SARS-CoV-2 infection, and to assess the persistence of antibodies following infection with another blood sample collected after 12 months. UK Biobank also performed repeat imaging of approximately 2,000 participants (half of whom had evidence of previous SARS-CoV-2 infection and half did not) to investigate the impact of the virus on changes in measures of internal organ structure and function. In addition, approximately 200,000 UK Biobank participants took part in a self-test SARS-CoV-2 antibody sub-study (between February and November 2021) to collect objective data on previous SARS-CoV-2 infection. These studies are enabling unique research into the genetic, lifestyle and environmental determinants of SARS-CoV-2 infection and severe COVID-19, as well as their long-term health effects. UK Biobank's contribution to the national and international response to the pandemic represents a case study for its broader value, now and in the future, to precision medicine research.